1702. Assessing the Safety and Efficacy of Valganciclovir Dosing for Cytomegalovirus Prophylaxis in Solid Organ Transplant Recipients on Hemodialysis. (31st December 2020) - Yee, Jason; Saunders-Hao, Patricia; Miko, Leandra; Rana, Meenakshi
Abstract: Background: Valganciclovir is the standard of care used for the prevention of Cytomegalovirus (CMV) infections among solid organ transplant (SOT) recipients. Currently there is minimal guidance for prophylaxis in SOT recipients undergoing intermittent hemodialysis (IHD). At Mount Sinai Hospital (MSH), the current practice for CMV prophylaxis in SOT recipients on IHD is valganciclovir 450 mg every other day (Q48H) or three-times weekly (TIW). This study aims to evaluate the safety and effectiveness of these dosing regimens in SOT recipients on IHD. Methods: A single-center, retrospective chart review study was conducted among all MSH SOT recipients on valganciclovir 450 mg Q48H or TIW for CMV prophylaxis and undergoing IHD for at least 30 days. The primary study outcome was the safety of using these valganciclovir doses determined by the incidence of leukopenia, thrombocytopenia, and the administration of growth colony stimulating factor (GCSF). The secondary outcome were the incidences of CMV viremia and CMV disease while on prophylaxis. Results: Eighteen transplant encounters satisfied the inclusion and exclusion criteria. The majority were liver (7, 38.9%) and kidney (5, 27.8%) transplants. Thirteen (72.2%) recipients were on valganciclovir 450 mg Q48H dosing, while 5 (27.8%) were on valganciclovir 450 mg TIW dosing. Both the mean platelet count nadir (131 ± 93 vs 161 ± 115) and mean white blood cell count nadir (3.4 ± 2.5 vs 5.1 ± 3.8) were lower in the Q48H regimen. Four patients (22.2%) in the Q48H regimen group required GCSF vs none (0.0%) in the TIW regimen. No patient had a detectable CMV viral load while on either prophylactic dose. Two (11.1%) CMV high risk patients on the every other day dosing regimen and one (5.6%) CMV moderate risk patient on the three times weekly regimen developed CMV viremia about 2-3 months after their prophylaxis was stopped. Table 1. Baseline Demographics. Table 2. Primary Outcomes Table 3. Secondary Outcomes Conclusion: Valganciclovir 450 mg TIW may be safer than and as efficacious as Q48H dosing for prophylaxis in SOT recipients on chronic IHD. This data supports the use of three times weekly dosing as standardized practice at MSH, however more data is necessary to determine a conclusive result. Disclosures: All Authors : No reported disclosures